PUBLIC OFFICIALS' UNLAWFUL ACT LAWSUITS AND PRESS FREEDOM THROUGH RESTORATIVE JUSTICE MECHANISMS - Natasya Dwi Nanda; Nuryati Solapari; Sariyah (Awang Long Law Review, 2026)
This study aims to analyze the normative tension between Article 1365 of the Indonesian Civil Code on unlawful acts and Press Law No. 40/1999, as well as to examine the implications of Constitutional Court Decision No. 145/PUU-XXIII/2025 for protecting press freedom from civil lawsuits filed by public officials. This tension arises because public officials and civil judges tend to disregard restorative justice mechanismssuch as the right of reply, correction right, and Press Council mediation which should serve as lex specialis in press disputes. Therefore, the urgency of this research lies in the pressing need for legal certainty for journalists facing SLAPP-type civil lawsuits. Employing a normative-juridical method with a prescriptive specification, along with statutory and case approaches, this study produces a novelty in the form of a mutual protection concept post-Constitutional Court decision that mandates restorative justice as an absolute prerequisite before civil lawsuits can be processed as a last resort. The results confirm that Constitutional Court Decision No. 145/PUU-XXIII/2025 constitutes a legal instrument shifting the paradigm of press protection from declarative-absolute to conditional-procedural, meaning that district court judges are obliged to declare civil lawsuits filed by public officials inadmissible if restorative justice mechanisms through the Press Council have not been pursued.